Management of Traumatic Ulcers in a Patient with Angle Class I Malocclusion: A Case Review - Juanna Soehardy; Thalia Angela; Emerentia Angela; How Kim Chuan; Susanna Halim (Postgraduate, University of Mataram, 2025)
Malocclusion is an inappropriate relationship of opposing teeth when the jaws are in contact. This malocclusion condition can cause oral cavity problems, one of which is traumatic ulcers. Traumatic ulcers are one of the most common lesions on the oral mucosa, where there is a loss of the epithelial layer beyond the basement membrane and affects the lamina propria which is generally caused by trauma. Traumatic ulcers can occur on the oral mucosa, including: on the tongue, lips, buccal mucosa folds, gingiva, palate, labial mucosa, buccal mucosa and floor of the mouth. The clinical picture of traumatic ulcers is not specific depending on the etiology, has a smooth surface, a yellowish lesion base and red margins and no induration. Ulcers usually heal without leaving a trace in 10-14 days, spontaneously or after eliminating the cause. Traumatic ulcers can occur at any age, both in men and women. The prevalence of traumatic ulcers is quite high. Several studies show variations in the range of 3 - 24% of the population. Management of traumatic ulcers is in the form of correcting predisposing factors. Local symptomatic treatment is the standard treatment for simple traumatic ulcers. Therapy in this case is to provide Oral Hygiene Instructions on the importance of maintaining dental and oral health. In addition, the patient was prescribed topical hyaluronic acid (Aloclair gel 8 ml) to reduce pain, povidone iodine antiseptic mouthwash and vitamin B12 to accelerate healing and the patient was asked to check 1 week after treatment. Summary of the results of traumatic ulcer therapy due to class I malocclusion with topical hyaluronic acid Aloclair gel 8 ml, antiseptic povidone iodine mouthwash, and vitamin B12 showed significant improvement in symptoms. Aloclair gel helps reduce pain and accelerate healing, while antiseptic mouthwash helps prevent infection. Vitamin B12 plays a role in accelerating the wound healing process.